A Sustainability 3D Framework of the 20 Regions of Italy and Comparison With World Countries - Pulselli, Federico M.; Sani, Alessandro; Goffetti, Giulia; Coscieme, Luca; Bastianoni, Simone (Frontiers in Energy Research, 2019)
An Input-State-Output framework has been recently introduced to investigate the multidimensional aspects of sustainability (namely environmental, social and economic ones) of economic systems through a thermodynamically and logically ordered scheme. This approach facilitates the convergence of information from sets of indicators without aggregating results into single numbers and, consequently, losing information. In this paper we experiment the application of the Input-State-Output framework for regional systems. In particular the 20 regions of Italy will be investigated, categorized and compared with each other. A triad of indicators is selected and calculated to represent the dimensions of sustainability. For the environmental dimension (input) we use Emergy, an energy-based accounting method that takes into account the flows of energy and matter feeding the system per unit time; for the social dimension (state) we use the Gini Index of income distribution as a proxy of the health status of a society as a whole and its organization; for the economic dimension (output) we use the Gross Regional Product or a similar measure, which represents the economic result of the system. As a general result, we identify and discuss the position of the systems under study, by means of the three coordinates within a 3D space, as well as the weaknesses and strengths of each indicator. We believe that this approach is able to give a more complete and rational view of sustainability. The application at the regional level can be of great help in identifying priorities and possible policies at both national and sub-national level.